Analysis Mother Knowledge with Risk Stunting Events in the Region Work Public health center Portibi - Ratna Wulandari; Yeni Zahara Harahap (International Journal of Public Health Excellence (IJPHE), 2023)
Based on SSGI (2019), several district / city with the highest prevalence of stunting in Indonesia, one of them is North Padang Lawas district with figure 53.3%, with case the most happen in the region Work Public health center Portibi (20.8%). stunt can be prevented with increase knowledge Mother about stunting prevention. Research objectives This For analyze connection knowledge Mother about nutrition with stunting in toddlers ages 24-36 months . Study This use method quantitative and cross sectional design . Population study This is mother who has toddler age 24-36 months in place stay in the region Work Public health center Cipadung . Amount sample in study This as many as 108 respondents . Taking sample use technique sample random simple . Statistical test used  in study This is the chi square test. There are 32.4% of toddlers who experience stunting, and some big Mother own knowledge tall about nutrition that is by 62%. There is a relationship between knowledge Mother about nutrition with stunting incidence (p=0.027, and OR=2.7). Mother who has knowledge low about nutrition 2.7 times the chance of his son experiencing stunting compared with mother who has knowledge tall about nutrition.